Evaluation of contributing factors towards landslide risk at UiTM Sabah Branch, Kota Kinabalu Campus / Ir Basir Noordin, Prof. Dr. Roslan Zainal Abidin and Mohd Fairuz Bachok - Noordin, Basir; Zainal Abidin, Roslan; Bachok, Mohd Fairuz (Research Management Institute (RMI), 2002)
Recently, the state of Sabah is facing a serious problem with landslides occurrence. With rapid development from government and private sector, this activity will worsen the said problems. However, with good planning and management on the development programme, the landslide problems can be minimized. As such, a research titled "Evaluation of Contributing Factors Towards Landslide Risk at UiTM Sabah Branch, Kota Kinabalu Campus u was carried out to identify the factors causing landslide. The scope of the research is to analyse all the factors such as rainfall, soil composition, land use, slope length and slope steepness at the campus. From the study, it is found the main factors contributing towards landslide event in the campus area are rainfall and soil composition. Other factors such as land use, slope steepness and slope length are also contributing towards landslide but at a very minimal degree. Therefore, it is hoped that the outcome of this research will highlight the important of knowing the actual care of any landslide occurrence in our country rather than blaming the nature besides taking into consideration the possibility of human disturbance.